2020
DOI: 10.7498/aps.69.20191973
|View full text |Cite
|
Sign up to set email alerts
|

Partial synchronization in complex networks: Chimera state, remote synchronization, and cluster synchronization

Abstract: In recent years, the study of partial synchronization of coupled oscillators in complex networks has attracted great attention. The underlying reason is both the extensive existence of the patterns of partial synchronization in brain network and their close relationship to brain functions of cognition and memory. In this paper, we briefly review the research progress in this field. According to the researches by different groups, we classify them as three types, i.e. chimera state, remote synchronization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…In accordance with coupled wave theory, out of sync is the norm in the innovation ecosystem [58]. If there is coupling fluctuation, there is a synchronous state in a local area [59].…”
Section: Deduction Of the Local Synchronous Agglomeration Modelmentioning
confidence: 82%
“…In accordance with coupled wave theory, out of sync is the norm in the innovation ecosystem [58]. If there is coupling fluctuation, there is a synchronous state in a local area [59].…”
Section: Deduction Of the Local Synchronous Agglomeration Modelmentioning
confidence: 82%
“…To understand the underlying mechanism of these three features or how the local topologies of nodes influence their behaviors, we recall the recent findings of cluster synchronization that the oscillators of network will be automatically evolved into different synchronized clusters but the oscillators in different clusters are not synchronized with each other [ 29 , 30 ]. It was revealed that network symmetry is the necessary condition for synchronized clusters [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The asymmetry of complex systems has a crucial impact on their collective behaviors. [22] Asymmetry can arise not only through the system's special network topology, but also through asymmetric coupling. In practical applications, asymmetric coupling widely exist in complex systems such as signal transmission, [23] brain neural networks, [24] swarm intelligence networks, [25] and biomolecular motors, [26] and produce rich group effects, such as stochastic resonance (SR), cluster synchronization, etc.…”
Section: Introductionmentioning
confidence: 99%